IMPLIKASI PENGGUNAAN KECERDASAN BUATAN TERHADAP HAK EKONOMI PENCIPTA DALAM INDUSTRI HIBURAN DI INDONESIA: ANALISIS UNDANG - UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA DAN UNDANG -UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Akh Edy Ismanto; Husein Manalu (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Artificial Intelligence (AI) has transformed the production, distribution, and monetization of creative works in the digital entertainment industry while raising legal issues concerning the use of copyrighted works as training data, AI-generated content, voice cloning, and the protection of authors' economic rights. This study aims to analyze the implications of AI for authors' economic rights in Indonesia's digital entertainment industry and to evaluate the adequacy of Law Number 28 of 2014 on Copyright and Law Number 11 of 2008 on Electronic Information and Transactions, as lastly amended by Law Number 1 of 2024. This research employs a normative juridical method using statutory, conceptual, and case approaches. The findings indicate that both laws do not specifically regulate the use of copyrighted works as training data, the legal status of AI-generated content, AI-based licensing and royalty mechanisms, or voice cloning. These findings reveal a legal gap, highlighting the need for a more adaptive regulatory framework to ensure legal certainty and strengthen the protection of authors' economic rights in the era of the digital entertainment industry.